Demonstrating the Effect of Supply Chain Disruptions through an Online Beer Distribution Game*. (January 2016) - Sarkar, Sourish; Kumar, Sanjay
ABSTRACT: This article describes a classroom tool to teach the impact of supply chain disruptions and mitigation strategies based on information sharing and collaboration. The tool is an adaptation of the Beer Distribution Game, is easy to play, and can be hosted online or on local servers. The game considers several scenarios based on the location of the disruptions (i.e., upstream or downstream) and the information available to supply chain partners. Students play the roles of managers who make ordering decisions in a serial supply chain and experience decision‐making under disruptions.